Simple and efficient synthesis of benzofuran derivatives from tyrosol. Issue 3 (1st February 2016) - Bovicelli, Paolo; Bottaro, Fabrizio; Sappino, Carla; Tomei, Michela; Nardi, Valentina; Proietti Silvestri, Ilaria; Macchi, Beatrice; Frezza, Caterina; Righi, Giuliana
ABSTRACT: A convenient strategy for the preparation of compounds bearing the benzofuran skeleton starting from tyrosol, a phenol largely present in olive oil production waste, with no biological importance, is reported. A bromination/methoxylation sequence, already described for the synthetic transformation of naturally occurring compounds, was exploited. Depending on the solvent used for the methoxylation reaction together with the presence of a 4-phenol moiety respect to the side chain, benzodihydrofurans or a benzofurans derivative can be obtained. GRAPHICAL ABSTRACT: